EP44 Taking eosinophilia more seriously. (20th April 2020) - Rutter-Locher, Zoe; Galloway, James; Menon, Bina; Goodman, Anna
Abstract: Background: Asymptomatic eosinophilia is common in migrants and travellers returning from the tropics, and helminth infection is the most common identifiable cause. Most helminth infections have a benign course, but some carry a risk of serious disease which is relevant to the rheumatologist as administration of immunosuppression can trigger severe reactions such as the potentially fatal hyper infection syndrome in strongyloidiasis. Helminth infections are of increasing relevance in an era of growing migration from endemic regions. A recent audit performed at a central London hospital in HIV outpatients found that of those patients with asymptomatic eosinophilia that were investigated, 28.6% had serological evidence of strongyloidiasis. Unexplained eosinophilia should be evaluated prior to starting immunosuppressive medications, especially in those who have lived in regions endemic for helminth infections. In 2010 the British Infection Society (BIS) published guidelines on the investigation of migrants and returning travellers with asymptomatic eosinophilia. We set out to establish how often our unit investigated unexplained eosinophilia prior to initiating immunosuppressive medication. Methods: All patients attending rheumatology outpatients at our centre were screened and included if they had a recorded eosinophilia of ≥ 0.8 X10 9 /L between December 2016 to December 2018. Patients were excluded if they did not have a sustained eosinophilia ≥0.8 X10 9 /L > 1 year or if another documented diagnosis was recognised as the cause of eosinophilia. Investigation of asymptomatic eosinophilia was compared to the best practice set out in British Infection Society guideline. Results: 109 patients fulfilled the inclusion criteria. 64 patients did not have a sustained eosinophilia > 1 year and 16 had an alternate diagnosis to explain eosinophilia and so were excluded. The remaining 29 patients were included. 13 patients were male and 16 female. 16 (55%) had a diagnosis of rheumatoid arthritis. 19 (66%) had an eosinophil count > 1 X10 9 /L and 7 (24%) > 2 X10 9 /L. Despite this, eosinophilia was only noted in documentation for 4 (14%) patients. Five (17%) patients had a travel history documented and 4 of them had travelled to the tropics. 3 (10%) patients were investigated for eosinophilia and only 1 (3%) was investigated fully according to the BIS guideline. 14 (48%) patients were on bDMARDs and a further 6 (21%) were on cDMARDs. Of the 14 (48%) on bDMARDS, 7 had ethnic origin in the tropics. Median eosinophil count was 1.2 x10 9 /L. One had travel history taken. All had a negative HIV test. None of the patients on biological therapy had investigations for eosinophilia. Conclusion: This study confirms the local lack of awareness of eosinophilia. Most patients with unexplained eosinophilia were not identified or investigated, even prior to administration of immunosuppressive medication. With a growing migrant population, the likelihood of serious consequences of ignoring eosinophilia are rising. Disclosures: Z. Rutter-Locher: None. J. Galloway: None. B. Menon: None. A. Goodman: None.